IMPLEMENTASI KEBIJAKAN APLIKASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Putra, Mahesa Dwi (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to examine the implementation of the Integrated DynamicArchival Information System Application (SRIKANDI) policy at theDepartment of Archives and Library of Sumedang Regency, identify theobstacles faced, and explore efforts made to overcome them. A qualitativemethod was used, with data collected through literature studies and fieldresearch, including in-depth interviews, observations, and documentation. Informants included the head of the department, head of the archival division, archival functionaries, and technical staff operating the SRIKANDI application. The findings indicate that SRIKANDI implementation has generally progressedwell in supporting digital archiving. However, challenges remain, such as limited IT infrastructure, lack of comprehensive staff training, and resistance toshifting from manual to digital systems. Integration with the previous archivingsystem is also suboptimal, causing overlapping workflows. To address thesechallenges, the department has improved human resource capacity throughtraining, provided necessary infrastructure, and conducted continuous outreachto promote understanding and commitment to digital transformation. The studyrecommends increasing budget allocation for IT infrastructure, providingequitable training for all staff, developing standard operating procedures(SOPs), and strengthening interdepartmental coordination to ensure moreeffective and sustainable implementation of the SRIKANDI application.